2008
DOI: 10.1016/j.febslet.2008.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a novel phosphopantetheinyl transferase domain in the polyketide synthase for enediyne biosynthesis

Abstract: The polyketide synthase associated with the biosynthesis of enediyne-containing calicheamicin contains a putative phosphopantetheinyl transferase (PPTase) domain. By cloning and expressing the C-terminal region of the polyketide synthase and in vitro phosphopantetheinylation assay, we found that the PPTase domain exhibits preferred substrate specificity towards acyl and peptidyl carrier proteins in fatty acid and non-ribosomal peptide synthesis over its cognate partner. We also found evidence suggesting that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…1, 4b, online resource 2). These findings are agreeable with the conserved roles of PPTase in post-translational activation of fatty acid synthases, polyketide synthases, and nonribosomal peptide synthetases (Liu et al 2005;Murugan and Liang 2008;Orikasa et al 2006); suggesting that the effect of ZmsO on zeamines production is mainly through modulation of the enzymes associated with zeamines biosynthesis. Since zeamines are the main virulence factor of D. zeae to cause the pathogenicity change between wild type strain EC1 and zmsO derived strains.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…1, 4b, online resource 2). These findings are agreeable with the conserved roles of PPTase in post-translational activation of fatty acid synthases, polyketide synthases, and nonribosomal peptide synthetases (Liu et al 2005;Murugan and Liang 2008;Orikasa et al 2006); suggesting that the effect of ZmsO on zeamines production is mainly through modulation of the enzymes associated with zeamines biosynthesis. Since zeamines are the main virulence factor of D. zeae to cause the pathogenicity change between wild type strain EC1 and zmsO derived strains.…”
Section: Discussionsupporting
confidence: 78%
“…Evidence is accumulating that post-translational modification of enzymes is necessary for biosynthesis of natural products by fatty acid synthases (Orikasa et al 2006), polyketide synthases (Murugan and Liang 2008), and nonribosomal peptide synthetases (Liu et al 2005). This modification is carried out by transformation of 4′-phosphopantetheine moiety from coenzyme A (CoA) to apo-carrier proteins (CPs) to form holo-carrier proteins by phosphopantetheinyl transferase (PPTase) (Beld et al 2014;Sunbul et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spore preparation of S. chattanoogensis L10 on YMG agar (0.4% yeast extract, 1% malt extract, 0.4% glucose, 2% agar, 0.2% CaCO 3 [pH 7.2]), the examination of NTM production in YEME with 4% glucose (0.3% yeast extract, 0.3% malt extract, 0.5% tryptone, 4% glucose), and DNA manipulations in S. chattanoogensis L10 were carried out according to standard procedures (25). Escherichia coli-Streptomyces conjugation, fermentation of S. chattanoogensis L10 and its recombinant strains, and quantification of NTM production were performed as described previously (11,15,20).…”
Section: Methodsmentioning
confidence: 99%
“…The release of the product catalyzed by the putative thioesterase SgcE10 presumably occurs through a combination of hydrolysis, decarboxylation, and dehydration steps. Recent biochemical studies of the iterative PKS (CalE8) from the biosynthetic pathway of calicheamicin also provided insight into the early steps of 10-membered enediyne biosynthesis (13,14). It was observed that CalE8 produced a linear carbonyl-conjugated polyene (3,5,7,9,11,13-pentadecen-2-one (1)) with the assistance of the putative thioesterase CalE7 (Fig.…”
mentioning
confidence: 99%